Optical and structural properties of ZnO hexagonal rods prepared by thermal chemical vapor deposition technique - A Reyhani; M. R Khanlary; V Vahedi (Iranian Journal of Physics Research, 2014)
In this research, ZnO nanostructure hexagonal pyramid rods with high optical and structural quality were synthesized by the simple thermal chemical vapor deposition of Zn powder without a metal catalyst. Surface morphologies were characterized by scanning electron microscopy (SEM). XRD analyses demonstrated that ZnO hexagonal pyramid rods had a wurtzite structure with the orientation of (002). Investigation of optical properties of samples by photoluminescence spectrum exhibited a sharp UV emission peak at 380nm. The quality and composition of the ZnO pyramid rods were characterized using the Fourier transform infrared spectrum (FTIR) at room temperature. In addition, the growth mechanism of ZnO hexagonal rods is also briefly discussed.